PENGARUH KEMAJUAN TEKNOLOGI INFORMASI DAN PENGETAHUAN INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSA NIPA - Maria Yosefina Sule; Yosefina Andia Dekrita; Kristiana Reinaldis Aek (Jurnal Projemen UNIPA, 2026)
This research aims to: (1) find out the overview of Investment Interests, Information Technology Advancements, and Investment Knowledge; (2) analyze the influence of Information Technology Advancement and Investment Knowledge on Investment Interest both partially and simultaneously. The population in this study is 1,280 students of the Faculty of Economics and Business, Nusa Nipa University. Based on the Slovin formula, the sample in this study amounted to 98 people. Sample distribution was carried out using proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using descriptive and statistical methods of multiple linear regression. Hypothesis testing is carried out through the F test and the t test. The results of the descriptive analysis showed that the Investment Interest variable was in the good criteria, the Information Technology Advancement variable was in the good criteria, and the Investment Knowledge variable was in the good criteria. The results of the t-test statistics show that partially the variable of Information Technology Advancement has a positive and significant effect on Investment Interest. Furthermore, the variable of Investment Knowledge has a positive and significant effect on Investment Interest. The statistical results of the F test show that simultaneously the variables of Information Technology Advancement and Investment Knowledge have a significant effect on Investment Interest. The results of the determination analysis showed that the two independent variables in this study were able to explain the variation in the fluctuation of Investment Interest in the Capital Market in students of the Faculty of Economics and Business, Nusa Nipa University by 33.2%. Keywords: Information Technology Advancement, Investment Knowledge, Investment Interest